The Effect of Tuition Fees on Student Enrollment and Location Choice – Interregional Migration, Border Effects and Gender Differences - Björn Alecke; Claudia Burgard; Timo Mitze (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper investigates the effects of tuition fees on the university enrollment and location decision of high school graduates in Germany. After a Federal Constitutional Court decision in 2005, 7 out of 16 German federal states introduced tuition fees for higher education. In the empirical analysis, we use the variation over time and across regions in this institutional change in order to isolate the causal effect of tuition fees on student enrollment and migration. Controlling for a range of regional- and university-specific effects, our results from Difference-in-Differences estimations show that there is generally no effect of tuition fees on internal enrollment rates. However, we find a redirecting effect on first-year students' migratory behavior as indicated by a signicant drop in the gross in-migration rates in fee-charging states. Further, our results point at a stronger migration response of male students, which, however, can mainly be attributed to a 'border effect'. That is, interregional migration flows of male students are redirected from fee-charging universities to those universities that are geographically close by while being located in a non-charging neighboring state. Controlling for these border effects, the relocating trend in long-distance migration of university freshmen does not show any particular gender differences. – – Diese Studie analysiert Effekte der Einführung von Studiengebühren in Deutschland auf das Einschreibe- und Mobilitätsverhalten von Studienberechtigten. Nach der Entscheidung des Bundesverfassungsgerichts im Jahr 2005, die das vorherige Gebührenverbot für verfassungswidrig erklärte, erhoben 7 von 16 Bundesländern Beiträge für ein Hochschulstudium. Die empirische Analyse nutzt die regionale Variation dieser Reform, um den kausalen Effekt der Gebühreneinführung auf Einschreiberaten und innerdeutsche Migration zu identifizieren. Nach Kontrolle für regionale als auch hochschulspezifische Effekte zeigen die Ergebnisse von Differenz-in-Differenzen-Schätzungen keinen generellen Effekt auf landesinterne Einschreiberaten. Allerdings wird ein Umverteilungseffekt bezüglich der Wanderung von Studienanfängern gefunden, welcher sich in einem signifikanten Rückgang der Brutto-Einwanderungsraten in Gebührenländer zeigt. Dieser Effekt ist für männliche Studienberechtigte stärker ausgeprägt und kann größtenteils einem 'Grenzeffekt' zugeschrieben werden. Dies bedeutet, dass Migrationsströme bei Männern von Gebührenländern umgeleitet werden, und zwar zu Hochschulen in benachbarten Nicht-Gebührenländern, die in der Nähe von Bundeslandgrenzen gelegen sind. Wenn für diesen Grenzeffekt kontrolliert wird, werden keine Geschlechterunterschiede im Wanderungsverhalten über längere Distanzen beobachtet.
Keywords: D04; I23; J16; R23; 330; tuition fees; gender differences; higher education; student migration; policy evaluation; Difference-in-Differences